Correlates of Success in World Bank Development Policy Lending - Moll, Peter (The World Bank, 2015)
This paper examines the correlates of success of development policy lending operations of the World Bank between 2004 and 2012. The paper uses a data set constructed of individual loan characteristics and ex-post loan ratings produced by the World Bank's Independent Evaluation Group. Departing from the related literature, the paper focuses mostly on examining the impact of loan characteristics, reform program design features, and task team leader skills, among other variables, on intended development results, while still controlling for country characteristics. It finds that a variable used to reflect congruence or "line of sight" between the policy reforms supported and the results framework is a critical ingredient for success. Task team leader skills in general, and task team leadership by staff affiliated with the former "Economic Policy" department of the World Bank, also increase the chance of success. Conversely, a weaker set of supported reforms in these operations tends to reduce the chance of success. Reforms supported in the energy sector seem to reduce the likelihood of success, perhaps because of the inherent political difficulties of implementing reforms in this sector. The paper also draws important policy and institutional implications from these and other findings